Assessment of knowledge about hypertension - Węgorowski, Paweł; Michalik, Joanna; Buchcic, Zbigniew; Stanisławek, Andrzej; Domżał-Drzewiecka, Renata (Journal of Education, Health and Sport, 2017)
Admission Epidemiological studies show that cardiovascular diseases are at the forefront of diseases affecting Polish society. Despite advances in modern medicine, every second person experiences acute or chronic cardiovascular complications. Purpose of research The purpose of this study was to assess patients’ knowledge of prevention, diagnosis and treatment of hypertension. Materials and methods The paper used the method of the diagnostic survey, within the framework of the survey technique, and as a research tool - questionnaire survey of its own author. The survey was conducted June - August 2015 in the Independent Public Health Care Team in Włodawa. 60 people participated in the study. The group was divided - 30 people with hypertension and 30 people who are not sick or healthy people. Conclusions In the study group, the level of knowledge about the factors influencing the occurrence of hypertension is high both among the sick and the healthy. Most patients with hypertension have a healthy lifestyle associated with proper nutrition, alcohol avoidance, smoking, lack of stress and rational rest. Among prevention activities, both the sick and the sick proposed similar treatment. Discussion Patient knowledge about hypertension and its effects can affect the effectiveness of treatment. Medical education should be of paramount importance for medical staff, with particular attention to the self-control of blood pressure by patients. In summary, it is important to note that due to the high risk of complications, both treatment and prevention of hypertension are important.